2020
DOI: 10.1111/1745-9133.12485
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential to reduce deaths and injuries from mass shootings through restrictions on assault weapons and other high‐capacity semiautomatic firearms

Abstract: Research Summary: This article examines the use, impacts, and regulation of assault weapons and other high-capacity semiautomatic firearms as they pertain to the problem of mass shootings in the United States. Highcapacity semiautomatics (which include assault weapons as a subset) are used in between 20% and 58% of all firearm mass murders, and they are used in a particularly high share of public mass shootings. Mass shootings perpetrated with these firearms result in substantially more fatalities and injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Additionally, Klarevas () found that, during 2006–2015 (after the federal ban expired), 67% of mass shootings with six or more victim fatalities involved the use of an LCM versus 26% with an assault weapon model. Based on the data from Koper (), Koper et al. (), and Klarevas (), our point estimates may be somewhat higher than would be plausible based on the prevalence of LCM use in fatal public mass shootings, although the confidence intervals for these estimates are wide and encompass the estimates of the prevalence of use of LCMs in fatal mass shootings.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Additionally, Klarevas () found that, during 2006–2015 (after the federal ban expired), 67% of mass shootings with six or more victim fatalities involved the use of an LCM versus 26% with an assault weapon model. Based on the data from Koper (), Koper et al. (), and Klarevas (), our point estimates may be somewhat higher than would be plausible based on the prevalence of LCM use in fatal public mass shootings, although the confidence intervals for these estimates are wide and encompass the estimates of the prevalence of use of LCMs in fatal mass shootings.…”
Section: Discussionmentioning
confidence: 73%
“…It is curious that these researchers did not examine whether the ban influenced the number of persons shot in mass shootings because the characteristics of the banned products are relevant to how many shots can be fired in a short span of time. Indeed, recent studies have documented that fatal mass shootings committed with assault weapons and/or LCMs result in significantly more victims shot than is the case in such shootings which involved no assault weapons or LCMs (Klarevas, ; Koper, , this issue; Koper, Johnson, Nichols, Ayers, & Mullins, ). DiMaggio and colleagues (2019) published a study in which they reported that during the period when the federal ban of assault weapons and LCMs was in place (1994–2004), fatal mass shootings were 70% less likely to occur.…”
mentioning
confidence: 99%
“…Researchers should investigate whether offenders used legally or illegally acquired firearms, how the weapons were acquired, the types of firearms or other weapon used, whether more than one type of weapon was used and if so how many and which ones, whether/how the weapons were modified to increase lethality, and what type of ammunition was employed, the size of the bullet/magazine, how it was acquired (again legally or illegally), how long it takes to shoot, how long it takes to reload. and for bombs what type of explosives were used, and if/how the ammunition was modified to increase deadliness, as well as if any specific type of explosive is associated with higher numbers of casualties (see also Koper, , this issue). This information could be used to create a scale of overall weapon deadliness (Taylor, ).…”
Section: Scp Terrorism and Preventing Or Reducing Public Mass Violencementioning
confidence: 99%
“…Although there are rational public safety grounds for restricting firearms with a variety of military‐style features, we believe the most important components of assault weapon laws are restrictions on large‐capacity ammunition magazines that enable shooters to discharge large numbers of rounds rapidly. Mass shootings and other crimes committed with high‐capacity semiautomatics (including assault weapons and other models) have been rising since the expiration of the federal ban on assault weapons, and this results in greater numbers of persons killed and wounded per incident as compared to attacks with other types of firearms (Koper, , this issue; also see Lankford & Silver, ). States with magazine capacity restrictions, however, have fewer mass shootings (Webster, McCourt, Crifasi, & Booty, , this issue).…”
Section: Staunching the Growth Of High‐capacity Firearmsmentioning
confidence: 99%